P-058 Risk factors associated with sperm DNA fragmentation in Tunisian subfertile men. (30th June 2022) - Boussabbeh, M; Ben Jmaa, M; Sallem, A; Belghaieb, I; Ammar, O; Mehdi, M
Abstract: Study question: The aim of the study was to investigate risk factors for sperm DNA fragmentation to determine which factors influence significantly the sperm DNA fragmentation. Summary answer: Obesity seems to lead to higher risk of sperm DNA damage in Tunisian subfertile men. What is known already: A positive association between lifestyle conditions, varicocele, advanced age and exposure to toxicants and DNA fragmentation has been documented. Study design, size, duration: It's a retrospective case control study. 61 Patients registered from October 2018 to December 2021 were divided into two groups: group "C" with good quality sperm DNA (n = 20) and group "F" with fragmented sperm DNA (n = 41). Participants/materials, setting, methods: DNA fragmentation was measured using terminal deoxynucleotidyltransferase dUTP nick and labeling assay. The Odds Ratio (OR) and their 95% CI were calculated using univariate logistic regression in order to quantify the association between the variable of interest "Sperm DNA fragmentation" and the various risk factors: lifestyle conditions (e.g. tobacco smoking, alcohol consumption, and obesity), age, professional exposure to high temperature and toxic products and urological history (e.g. varicocele, testicular hypotrophy or hypertrophy). Main results and the role of chance: Our results showed that tobacco, professional exposure to high temperature and toxic products and urological history are risk factors that may alter sperm DNA with an odds ratio (OR) of 2.1, 1.9 and 1.5, respectively. Interestingly, we demonstrated that obesity seems to be the most significant risk factor of DNA fragmentation with an OR of 4.2 (p = 0.002). Limitations, reasons for caution: Further studies are needed to investigate the mechanism by which obesity occur sperm DNA damage. Wider implications of the findings: Our finding are in accordance with several retrospective studies demonstrating that obesity is liable to sperm DNA damage Trial registration number: not applicable